Mechanisms ‘all the way down’? - Muntean, Ioan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
Book review: Mechanistic Explanations in Physics and Beyond, Brigitte Falkenburg and Gregor Schiemann, editors, European Studies in Philosophy of Science, Vol. 11, Springer International Publishing, Cham 2019, pp.220